Polysaccharides from natural resource: ameliorate type 2 diabetes mellitus via regulation of oxidative stress network - He, Li-Ying; Li, Yong; Niu, Shu-Qi; Bai, Jing; Liu, Si-Jing; Guo, Jin-Lin (Frontiers in Pharmacology, 2023)
Diabetes mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia that can occur in children, adults, elderly people, and pregnant women. Oxidative stress is a significant adverse factor in the pathogenesis of DM, especially type 2 diabetes mellitus (T2DM), and metabolic syndrome. Natural polysaccharides are macromolecular compounds widely distributed in nature. Some polysaccharides derived from edible plants and microorganisms were reported as early as ten years ago. However, the structural characterization of polysaccharides and their therapeutic mechanisms in diabetes are relatively shallow, limiting the application of polysaccharides. With further research, more natural polysaccharides have been reported to have antioxidant activity and therapeutic effects in diabetes, including plant polysaccharides, microbial polysaccharides, and polysaccharides from marine organisms and animals. Therefore, this paper summarizes the natural polysaccharides that have therapeutic potential for diabetes in the past five years, elucidating their pharmacological mechanisms and identified primary structures. It is expected to provide some reference for the application of polysaccharides, and provide a valuable resource for the development of new diabetic drugs.